2000
DOI: 10.1063/1.870284
|View full text |Cite
|
Sign up to set email alerts
|

Scattering and radiation of water waves by permeable barriers

Abstract: The two-dimensional problems of scattering and radiation of small-amplitude water waves by thin vertical porous plates in finite water depth are considered using the linear water wave theory. Applying the method of eigenfunction expansion, these boundary value problems are converted to certain dual series relations. Solutions to these relations are then obtained by a suitable application of the least squares method. For the scattering problem, four different basic configurations of the barriers are investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
29
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(35 citation statements)
references
References 23 publications
6
29
0
Order By: Relevance
“…The scattering and generation of waves by permeable barriers are well studied in the recent literature [12][13][14] under the assumptions of the linearised theory of water waves in a singlelayer fluid of finite depth. However, negligible progress has been made in the literature on the study of wave past porous structures in a two-layer fluid having a free surface and interface.…”
Section: Introductionmentioning
confidence: 99%
“…The scattering and generation of waves by permeable barriers are well studied in the recent literature [12][13][14] under the assumptions of the linearised theory of water waves in a singlelayer fluid of finite depth. However, negligible progress has been made in the literature on the study of wave past porous structures in a two-layer fluid having a free surface and interface.…”
Section: Introductionmentioning
confidence: 99%
“…Isaacson et al [8] later extended their theory to the wave scattering by double slotted barriers. Lee and Chwang [9] and Sahoo et al [10] , using a method similar to Isaacson et al [1] , studied the reflection and transmission of regular waves by partially submerged permeable barriers.…”
Section: Introductionmentioning
confidence: 98%
“…Kanoria et al (1999) discussed the problem involving scattering of water waves by different kinds of thick vertical barriers. Sahoo et al (2000) and Lee and Chwang (2000) discussed the problem of water wave scattering by vertical permeable barriers with the help of eigenfunction expansion method. Yip et al (2002) discussed the trapping of surface waves by vertical porous and flexible barrier and observed that the deflection at the free end is smaller for the bottom touching barrier than for the surface-piercing barrier.…”
Section: Introductionmentioning
confidence: 99%